The Correlation Between Body Fat Percentage and Peak Expiratory Flow in Children Aged 10-12 Years At SD Negeri 8 Dauh Puri - Ni Wayan Melyani Indahswari; Agung Wiwiek Indrayani; Ari Wibawa; Sayu Aryantari Putri Thanaya (Master of Epidemiology, School of Postgraduate Studies, Diponegoro University, Indonesia, 2019)
Background: The accumulation of fat decreases lung function. Peak expiratory flow is an indicator for assessing pulmonary function and can be used to identify the narrowing or obstruction of the airway. This study aimed to examine the correlation between body fat percentage and peak expiratory flow in children aged 10-12 years.Methods: This study was an analytical study with a cross-sectional design carried out in March 2019 at SD Negeri 8 Dauh Puri, Denpasar. Sampling was done by simple random sampling, and 84 samples were recruited who met the inclusion and exclusion criteria. Body fat percentage was measured using Bioelectric Impedance Analysis, while peak expiratory flow was measured using Peak Flow Meters. Data analysis was done using the Pearson Correlation test..Result: The Pearson Correlation Test showed a negative weak correlation between the percentage of body fat and peak expiratory flow with p=0.009 and a correlation coefficient of -0.284. It can be interpreted that the higher the body fat percentage, the higher the value of peak expiratory flow.Conclusion : There is a significant correlation between body fat percentage and peak expiratory flow in children aged 10-12 years at SD Negeri 8 Dauh Puri.